2018
DOI: 10.1063/1.5020173
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically Induced Transparency (EIT) and Autler-Townes (AT) splitting in the presence of band-limited white Gaussian noise

Abstract: We investigate the effect of band-limited white Gaussian noise (BLWGN) on electromagnetically induced transparency (EIT) and Autler-Townes (AT) splitting, when performing atom-based continuous-wave (CW) radio-frequency (RF) electric (E) field strength measurements with Rydberg atoms in an atomic vapor. This EIT/AT-based E-field measurement approach is currently being investigated by several groups around the world as a means to develop a new SI traceable RF Efield measurement technique. For this to be a useful… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 18 publications
2
20
0
2
Order By: Relevance
“…Furthermore, there are indications that this Rydberg atom-based system may be less susceptible to noise. As was the case in measuring CW electric-field strengths 19 , where we performed experiments measuring CW E-field strengths using this atom-based approach in the presence of band-limited white Gaussian noise and we showed that the E-field strength could be detected in low CW-signal to noise-power ratio conditions. The detection scheme discussed here can be improved by reducing laser noise and systematic effects, which is the topic of future work.…”
mentioning
confidence: 59%
“…Furthermore, there are indications that this Rydberg atom-based system may be less susceptible to noise. As was the case in measuring CW electric-field strengths 19 , where we performed experiments measuring CW E-field strengths using this atom-based approach in the presence of band-limited white Gaussian noise and we showed that the E-field strength could be detected in low CW-signal to noise-power ratio conditions. The detection scheme discussed here can be improved by reducing laser noise and systematic effects, which is the topic of future work.…”
mentioning
confidence: 59%
“…The atom-based receiver interacts with noise in a different manner than conventional systems and as such may be less susceptible to noise. This is indicated in [24], [27], where E-field strengths and modulated signals could be measured and detected in the presence of band-limited white Gaussian noise for low CW-signal to noise-power ratio conditions. While the bandwidth of these Rydberg-atom receivers/sensors depend on the Rydberg state chosen, in general, the bandwidth is limited by the response time of the atomic transition, which is on the order of 10 MHz [29], [39], and [40].…”
Section: Discussionmentioning
confidence: 98%
“…However, we can make a few preliminary observations concerning some of the aspects of Rydberg atom-based systems. Rydberg atom-based receivers and sensors have potential advantages over conventional radio technologies, which include: (1) micron-size sensors over a frequency range of 500 MHz to 1 THz [6], [7], (2) multiband (or mutli-channel) operation in one compact vapor cell [27], [38], (3) the possibility of being less susceptible to noise [24] and [27], (4) ultra-high sensitivity reception from 500 MHz to 1 THz [28] with sub Hz frequency resolution, and (5) no need for traditional down-conversion electronics because the atoms automatically down-convert the phase modulated signals to an IF. Furthermore, the Rydberg atom-based receiver has the possibility of being less affected by ''spoofing'' and ''jamming'' (as well as noise) when compared to conventional systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We (and others) have made significant progress in the development of new radio frequency (RF) electric (E) field strength and power metrology techniques based on the large dipole moments associated with Rydberg states of alkali atomic vapor [either cesium ( 133 Cs) or rubidium ( 85 Rb)] placed in glass cells [2]- [20]. In this approach, we use the phenomena of electromagnetically induced transparency (EIT) for the E-field sensing.…”
Section: Introductionmentioning
confidence: 99%